Improvement Model to Increase Productivity Based on the Application of SLP and Lean Manufacturing Tools in a Textile Company - Cabrera-Jeronimo, Jordan (2023)
Currently, the textile industry worldwide is one of the most important for the development of emerging countries. However, like many industries, it is not exempt from the presence of various problems, the most frequent being the presence of low levels of productivity. Which influence the ability of organizations to satisfy the demanding current market. Therefore, in order to address this problem, a plant distribution improvement model was proposed based on the application of methodologies such as Lean Manufacturing and Systematic Layout Planning. From these, an increase in productivity rates was generated through the proper management of resources and processes under a continuous improvement approach.